2016
DOI: 10.1007/s10164-016-0488-2
|View full text |Cite
|
Sign up to set email alerts
|

Space use and social ecology of coyotes (Canis latrans) in a high-elevation ecosystem: relative stability in a changing environment

Abstract: Coyote (Canis latrans) spatial and social ecology are variable, but have been little studied in high-elevation environments. In these temperate ecosystems, large ungulates are prevalent and coyote pack size may be large in order for them to scavenge and defend ungulate carcasses from conspecifics in neighboring packs. We initiated a study to understand the spatial and social ecology of coyotes on the Valles Caldera National Preserve, a high-elevation (2450-3400 m) protected area in northern New Mexico. Our obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Increased variability observed in transient movements may have resulted from extensive movements associated with long‐distance dispersal (Hinton et al., 2012) and shifting space use (Hinton et al., 2015). Previous studies have reported temporal and spatially consistent patterns in both space use and movements of resident coyotes throughout their annual cycle (Gifford et al., 2017; Hinton et al., 2015; Young et al., 2006). Conversely, transiency is characterized by nomadic movements where transient individuals may avoid residents while also searching the landscape for vacant territories (Hinton et al., 2015; Morin & Kelly, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Increased variability observed in transient movements may have resulted from extensive movements associated with long‐distance dispersal (Hinton et al., 2012) and shifting space use (Hinton et al., 2015). Previous studies have reported temporal and spatially consistent patterns in both space use and movements of resident coyotes throughout their annual cycle (Gifford et al., 2017; Hinton et al., 2015; Young et al., 2006). Conversely, transiency is characterized by nomadic movements where transient individuals may avoid residents while also searching the landscape for vacant territories (Hinton et al., 2015; Morin & Kelly, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…and shifting space use (Hinton et al, 2015). Previous studies have reported temporal and spatially consistent patterns in both space use and movements of resident coyotes throughout their annual cycle (Gifford et al, 2017;Hinton et al, 2015;Young et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…2003, Gifford et al. 2017). All of these factors combined suggest that coyotes can provide more regular long‐distance dispersal opportunities than other sympatric seed dispersers that may offer more irregular but longer distance dispersal (Escribano‐Avila et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two species that require cold stratification never emerged, C. ehrenbergiana seeds had no reduction in total emergence for any gut passage duration. Coyotes can regularly travel 7 km or more in 24 h (Young et al 2006) and even average 0.94 km/h of net displacement (Kitchen et al 2000) within home ranges of between 10 and 16 km 2 (Chamberlain et al 2000, Gosselink et al 2003, Gifford et al 2017. All of these factors combined suggest that coyotes can provide more regular long-distance dispersal opportunities than other sympatric seed dispersers that may offer more irregular but longer distance dispersal (Escribano-Avila et al 2014).…”
Section: Controlmentioning
confidence: 99%
“…DISCUSSION-Elk was an important food item and, as with rodents, we detected it in coyote scats during all months of the study. At the time of our study, coyote persecution had recently ceased (in 2000), so coyotes may have shifted their activity patterns (Kitchen et al, 2000) and habitat use to overlap more with elk diurnal use of open meadow habitats (Gifford et al, 2017). Based on our field observations, coyote consumption of elk calves resulted from a combination of predation and scavenging.…”
mentioning
confidence: 84%